2017
DOI: 10.2147/copd.s150887
|View full text |Cite
|
Sign up to set email alerts
|

Doxofylline is not just another theophylline!

Abstract: Doxofylline, which differs from theophylline in containing the dioxalane group at position 7, has comparable efficacy to theophylline in the treatment of respiratory diseases, but with an improved tolerability profile and a favorable risk-to-benefit ratio. Furthermore, it does not have significant drug–drug interactions as exhibited with theophylline, which make using theophylline more challenging, especially in elderly patients with co-morbidities receiving multiple classes of drug. It is now clear that doxof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 37 publications
4
54
0
Order By: Relevance
“…The results of the present meta-analysis are not surprising considering that doxofylline should not be assumed just as another theophylline [14]. It is now well established that doxofylline possesses a distinct pharmacological profile from theophylline (table 1 and figure S4).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The results of the present meta-analysis are not surprising considering that doxofylline should not be assumed just as another theophylline [14]. It is now well established that doxofylline possesses a distinct pharmacological profile from theophylline (table 1 and figure S4).…”
Section: Discussionsupporting
confidence: 59%
“…Given the pharmacological profile of doxofylline [49,50]; its significant anti-inflammatory activity that can result in significant steroid sparing activity, as documented at least in both an allergic and a nonallergic murine model of lung inflammation [54]; its documented clinical activity [12][13][14]; and, above all, the results of the present meta-analysis, there is a clear need to understand what is the room in the treatment of COPD for a xanthine that induces the same, if not even better, therapeutic effects of theophylline but with a totally different safety profile. Specifically, the rate of study withdrawal due to adverse events such as dyspepsia, epigastralgia, nausea and palpitation was approximately four-fold higher in COPD patients treated with theophylline than in those treated with doxofylline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to theophylline, administration of doxofylline does not increase the frequency of cardiac events, and patients show improved tolerability and a favourable risk-to-benefit ratio. Thus, doxofylline has better efficacy and fewer side effects, making it a promising bronchodilator [11]. Preclinical research has shown that doxofylline inhibits LPSinduced lung inflammation in mice [12].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with theophylline, doxofylline has a dioxalane group at position 7. Doxofylline has improved efficacy as compared to theophylline but shows fewer side effects and is viewed as a replacement for theophylline [11]. Doxofylline possesses potent anti-inflammatory and bronchodilatory activities, and it acts as a non-selective phosphodiesterase (PDE) inhibitor.…”
Section: Introductionmentioning
confidence: 99%